A Study of the Construction of Female Identity: John Fowles’ The French Lieutenant’s Woman - Golestani, Narjes Tashakor (Ciência e Natura, 2015)
The issue of identity and female consciousness as one of the major concerns of feminists has always been polemical, for there are different attitudes in formulating gender identity and consequently defining what a woman is. As its theoretical framework, this study relies on Judith Butler’s theory of gender and sexuality and studies the construction of identity in the female characters of John Fowles’ The French Lieutenant’s Woman. Judith Butler, a feminist constructivist, stresses the effect of socially constructed gender roles on creating gender identity and proposes her performative theory of gender and sexuality. In her theory Butler argues that gender is not what one is but what one does. In this sense, gender is not a stable identity from which various acts proceed; rather it is an identity constituted through a stylized repetition of normative gender roles and performances. Regarding gender as performative reveals that, what is taken as an internal essence of gender is actually fabricated through the regulatory frame of interacting discourses. It has an imitative structure which can be deconstructed. The study, thus, focuses on the effect of prescribed gender roles and norms in the process of identity formation, and examines Ernestina Freeman as a conformist character who constitutes her identity by taking on the ideal gender norms of the era and Sarah woodruff who tries to renegotiate and reenact those roles and constructs a sense of self which transcends constraints of the social and cultural hegemonic frame.